Implementasi Kebijakan Pemberdayaan Masyarakat melalui Program Padat Karya pada Satuan Kerja Pelaksanaan Jalan Nasional - Yuliana Yuliana (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to analyze the implementation of community empowerment policies through labor-intensive programs in the national road implementation work unit which was carried out in Region I, South Sumatra Province. The method used is descriptive research with a qualitative approach. Collecting data using interview, observation and documentation methods. Data analysis was carried out in an interactive form on 3 main components, namely; Data reduction, data presentation and conclusion drawing. The results of the study indicate that implementation can be seen from 2 indicators, namely: Policy content and implementation context. From this research it was found that: (1). The implementation of community empowerment policies through labor-intensive programs has been going well but has not been maximized; (2). Factors that strengthen the implementation of labor-intensive programs are information and counseling. The conclusion of the study shows that if we look at Grindle's theory, the implementation of community empowerment policies through labor-intensive programs in the national road implementation work unit has been going well but not optimally. Keywords: Community Empowerment, Implementation, Padat Karya.